2006
DOI: 10.1097/00024665-200609000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Nursing Language in the Systematized Nomenclature of Medicine Clinical Terms

Abstract: Many standardized healthcare languages have been mapped to the Systematized Nomenclature of Medicine Clinical Terms known as SNOMED CT, which was developed by the College of American Pathologists. This study describes a methodology for detecting misassigned concepts from source systems to SNOMED CT and presents the results of applying this methodology to a subset of concepts from two standardized nursing languages, the Nursing Interventions Classification and the Nursing Outcomes Classification. The methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…Evaluation of the nursing concepts in SNOMED continued for another decade [47,48]. Later research has evaluated the differences between nursing concepts within SNOMED-CT [49,50]. After years of work, nursing terminology was well integrated into the common nomenclature (UMLS).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the nursing concepts in SNOMED continued for another decade [47,48]. Later research has evaluated the differences between nursing concepts within SNOMED-CT [49,50]. After years of work, nursing terminology was well integrated into the common nomenclature (UMLS).…”
Section: Discussionmentioning
confidence: 99%
“…We defined “medication” to refer to all prescription and over-the-counter drugs, supplements, and herbal products. Unlike other terminology validation studies in which the terminology to be validated existed prior to validation, 3032 our study attempted to validate the use of concepts from one domain of healthcare (pharmacy) in another domain (medicine).…”
Section: Methodsmentioning
confidence: 99%
“…Lack of consistent terminology has been cited as a factor in the marginalization of certain concepts in contemporary nursing practice (Webber 2009). Other authors have identified the importance of standardized nursing language in improving patient safety, increasing quality, enhancing visibility of nursing care, and improved evaluation of the impact of nursing care on outcomes (Lu et al 2006, Jiang et al 2007, Rutherford 2008. Our findings are consistent with the suggestion that variations in terminology can contribute to variations in practice.…”
Section: Implications For Nursingmentioning
confidence: 99%